Relationship between vitamin C ingestion and antioxidant enzymes in obese women (Research, Society and Development, 2021)
The present study aimed to assess the relationship between dietary vitamin C intake and activity of antioxidant enzymes in obese women. This is a case-control study, involving 62 women, aged between 20 and 50 years, divided into two groups: control group (eutrophic women, n = 40) and case group (obese women, n = 22). The measures of weight and height were considered to calculate the body mass index, as well as the estimated intake of calories, macronutrients and vitamin C. In addition, blood samples were collected from the participants for further analysis of the erythrocyte activity of the enzymes glutathione peroxidase and superoxide dismutase. The data were analyzed using the statistical program SPSS for Windows 22.0. As for the results, a statistically significant difference was observed regarding the consumption of carbohydrates and lipids (p